A virus responds instantly to the presence of the vector on the host and forms transmission morphs - Alexandre Martinière; Aurélie Bak; Jean-Luc Macia; Nicole Lautredou; Daniel Gargani; Juliette Doumayrou; Elisa Garzo; Aranzazu Moreno; Alberto Fereres; Stéphane Blanc; Martin Drucker (eLife, 2013)
Many plant and animal viruses are spread by insect vectors. Cauliflower mosaic virus (CaMV) is aphid-transmitted, with the virus being taken up from specialized transmission bodies (TB) formed within infected plant cells. However, the precise events during TB-mediated virus acquisition by aphids are unknown. Here, we show that TBs react instantly to the presence of the vector by ultra-rapid and reversible redistribution of their key components onto microtubules throughout the cell. Enhancing or inhibiting this TB reaction pharmacologically or by using a mutant virus enhanced or inhibited transmission, respectively, confirming its requirement for efficient virus-acquisition. Our results suggest that CaMV can perceive aphid vectors, either directly or indirectly by sharing the host perception. This novel concept in virology, where viruses respond directly or via the host to the outside world, opens new research horizons, that is, investigating the impact of ‘perceptive behaviors’ on other steps of the infection cycle.